Homocistinuria. Algunos aspectos del tratamiento dietético. - Valdés Girona, Beatriz; Martínez Torres, Eric; Pascual Gispert, Joaquin (Revista Cubana de Pediatría, 2024)
Mostrar los resultados de 3 años de tratamiento.